Production and Waste Management for Initiation of Green Campus Program at Universitas Negeri Malang. Issue 1 (May 2019) - Novianti, Vivi; Wayan Sumberartha, I; Amin, Muhammad
Abstract: In 2017, Universitas Negeri Malang (UM) was declared as a green campus, which is a concept developed for environmental management. It is necessary to provide data and information on environmental management at UM to support the green campus. One of them is the problem of waste and its management. The purpose of this study was to determine the amount and type of waste, analyze the factors that affect the production and management of waste, and develop waste management strategies at UM. The research approach included surveys, observations, questionnaires, random interviews on all campus elements in nine faculties. The data were processed and analyzed descriptively. The amount of waste generated at UM was 1.5-2.0 tons per day and increased two times higher at a special event. The garbage produced in the form of organic (50%) and inorganic waste (50%). Organic waste consisted of leaves and food scraps, while inorganic waste included plastic (food wrap and bottles of mineral water), cardboard, and paper. The sorting of the type of garbage only occurred inside the campus; it would be re-mixed in landfills. Therefore, waste management at UM has been dominated by a conventional method (collecting, transporting, and disposing of) with landfilling as the final dumping. Some strategies were needed in the form of building the integrated waste management centers, socialization of sustainable campus waste management, integration of environmental knowledge in specific courses in each study program, and green programs carried out jointly by the campus community to realize UM as a green campus.